PRESCRIBED SURFACE TEMPERATURE AND PRESCRIBED HEAT FLUX ANALYSIS OF JEFFREY FERROFLUID FLOW OVER VERTICAL STRETCHABLE PLATE WITH MAGNETIC DIPOLE EFFECT (The Transactions of the Nigerian Association of Mathematical Physics, 2025)
The flow of Jeffery ferrofluid over a vertical stretching sheet in the presence of magnetic dipole and suction/injection was considered. Similarity transformations transformed the governing equations into nonlinear ordinary differential equations which were solved using the Chebyshev spectral collocation method. Effects of the existing parameters on the flow and heat transfer were presented in graphs and tables. Results obtained were compared with those in the literature and showed good agreement. Grashof number increased fluid velocity and reduced fluid temperature, it increased Nusselt number and decreased skin friction. Magnetic dipole reduced velocity and increased temperature. The Suction parameter (S > 0) reduced Nusselt number and increased skin friction. These findings are useful in industrial applications such as the cooling of voice coils in loudspeakers and magnetic hyperthermia.